(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to assess the knowledge and practices of nurses regarding fall prevention for patients at Da Nang Oncology Hospital. Describing related factors. Materials and methods: A cross-sectional research was carried out between March and August 2024, including 106 nurses from the clinical departments of Da Nang Oncology Hospital. Data were collected using structured questionnaires assessing nurses’ knowledge and practices related to fall prevention. Results: The average age of the participants was 33.3 years (± 4.4), with an average professional experience of 9.5 years (± 4.3). The majority of participants were female (98.1%) and cared for an average of 19.1 ± 5.9 patients per day. The mean knowledge score was 15.2 ± 2.0, with 86.8% of nurses meeting the knowledge standard. The mean practice score was 71.5 ± 12.2, with 83.0% demonstrating adequate practices. A statistically significant relationship was observed between the number of patients cared for daily and both knowledge and practice scores (p < 0.05). Additionally, a strong correlation was found between knowledge and practice scores (p < 0.001). Conclusion: Most nurses at Da Nang Oncology Hospital demonstrated adequate knowledge (86.8%) and satisfactory practices (83.0%) In patient fall prevention. The number of patients cared for daily significantly influenced these outcomes. Regular training programs and targeted support, particularly in high-workload settings, are recommended to enhance fall prevention effectiveness and ensure patient safety.